NUTRITIVE VALUE, ACCEPTABILITY, ANTIOXIDANT ACTIVITY AND STORAGE STABILITY OF HIBISCUS ROSA SINENSIS INCORPORATED READY TO EAT POWDERS - P., Nisha; Sheela, S. (International Journal of Current Pharmaceutical Research, 2015)
Objectives: Hibiscus rosa sinensis possess many properties and this plant may procured at large scale for providing herbal alternative to many diseases. The study was planned to prepare value added ready to eat powders by incorporation of Hibiscus rosa sinensis. The flowers of Hibiscus were processed and dried powder was incorporated into commonly prepared ready to powders namely Chutney powder, Avalose powder and Prawn powder at a ratio of 10%, 20% and 30% respectively. Methods: Organoleptic and quantitative analysis was screened in Hibiscus incorporated ready to eat foods. Results: Evaluation of organoleptic of the formulated powders showed that the incorporation of hibiscus at 10% was highly acceptable in terms of appearance, colour, flavour, texture and taste. The increase in nutrient content on incorporation of hibiscus at 10% was found to be 3.83 kcal,16.57 kcal and 0.25 kcal of energy; 0.24g, 1.18g and 0.58g of protein; 1.85g, 1.76g and 0.33g of fat in chutney powder, prawn powder and avalose powder respectively. The minerals were also increased by incorporating hibiscus at 10% which was found to be 4 mg, 12 mg and 1.06 mg of calcium; 8.02 mg, 14 mg and 8.22 mg of phosphorous; 0.8 mg 1.35 mg and 1.65 mg of iron; 4.33 mg, 5 mg and 18 mg of potassium and 0.6 mg, 1.2 mg and 0.5 mg of vitamin C in chutney powder, prawn powder and avalose powder respectively. Avalose powder had maximum phenolic content (1.04 mg/100g) compared with chutney powder (1.57 mg/100g) and prawn powder (1.04 mg/100g) and flavanoid content is high in chutney powder (2.96 mg/100g). The ready to eat powders had good shelf life at room temperature for a period of 30 d in LDPE. Conclusion: The incorporation of hibiscus at 10% was found to improve the nutrient content like energy, protein, fat, calcium, phosphorous, potassium, iron, vitamin c and antioxidant like total phenol and flavanoid. The shelf life of ready to eat powders stored in LDPE was good for 30 d. The bacterial growth was less in LDPE packaging.